2019
DOI: 10.1088/1742-6596/1358/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extraction sequence on yield and physico-chemical characteristic of chitosan from shrimp shell waste

Abstract: The focus of this study was to compare the yield and characteristics of chitosan produced from different sequences of treatment for deproteination, demineralization and deacetylation. In Process 1, deproteination occurred in the first step followed by demineralization and deacetylation. While Process 2 was started with demineralization step and followed by deproteination and deacetylation. The results show that the percentage yield of chitosan was slightly higher when Process 2 was adopted with 22.22 %. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…It almost exactly matches William and Wid's 35 findings, who found that the average amount of chitosan produced from the wet weight of shrimp shell waste was 19.01%. Because the natural structure of chitin (a protein) was lost during the deproteination process, less chitosan was generated when extraction was started with deproteinization.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It almost exactly matches William and Wid's 35 findings, who found that the average amount of chitosan produced from the wet weight of shrimp shell waste was 19.01%. Because the natural structure of chitin (a protein) was lost during the deproteination process, less chitosan was generated when extraction was started with deproteinization.…”
Section: Resultssupporting
confidence: 88%
“…The ratio of the dry weight of chitosan flakes to the wet weight of shrimp shell, as determined by Eq. ( 1 ), was used to calculate the chitosan yield (%) 35 : …”
Section: Methodsmentioning
confidence: 99%
“…This study observed that 60% NaOH applied in the deacetylation of chitin resulted in a solubility and DDA of 71.23% and 85.20%, respectively ( Table 4 ). The solubility and DDA of chitosan in this study would have been higher than the values obtained but for the relatively high ash content [ 64 ]. It is on record that the solubility and DDA of chitosan obtained from insect cuticle [ 18 ], deep sea mud [ 54 ], and fungi [ 65 ] are all lower than the results of the present study.…”
Section: Resultsmentioning
confidence: 75%
“…Due to intermolecular and intramolecular water traces, O–H and N–H peaks might overlap with each other to form a wide band that appeared in the same area for both groups (Figure 1). The C–H stretching, both symmetric and asymmetric, was observed at 2,921 to 2,875 cm −1 (William & Wid, 2019). For amide‐I, representing CO stretching from the acetyl group, it was observed at 1,650 cm −1 (Trung & Bao, 2015).…”
Section: Resultsmentioning
confidence: 99%